Utility of enhanced recovery after surgery protocols in reducing postoperative opioid use across different surgical specialties—An analysis of Iowa’s billion pill pledge program - Wali U. Pirzada; Simran Shamith; Roland N. Leyson; Sara A. Khan; Sina Ramtin; Asif M. Ilyas (PLoS ONE, 2025)
Introduction The opioid epidemic in the United States poses a major public health challenge, particularly in the context of surgery and perioperative pain management. This study examines the effectiveness of the “Billion Pill Pledge” Enhanced Recovery After Surgery (ERAS) protocols implemented across nine Iowa hospitals, in reducing postoperative opioid prescriptions. Methods A retrospective chart review was conducted on patients treated by 24 different surgeons at 9 Iowa hospitals from November 2022 to November 2023. Patients were divided into orthopaedic surgery (n = 120) and general surgery (n = 60) groups. Opioid quantities prescribed pre- and post-ERAS implementation were measured and converted to morphine milligram equivalents (MMEs). Statistical analyses included the Wilcoxon-Signed Rank test, Mann-Whitney U test, and Chi-Squared tests. Results The mean pre-ERAS prescription was 341 MMEs (range: 25–7200 MMEs), which decreased to 151 MMEs (range: 25–2400 MMEs) post-ERAS implementation (p < .001), following all surgeries. Orthopaedic Surgery patients saw a mean 45% reduction in prescription size from 462 MMEs (range: 50–7200 MMEs) to 197 MMEs (range: 25–2400 MMEs) (p < .001), while General Surgery patients experienced a mean 38% reduction from 100 MMEs (range: 25–150 MMEs) to 60 MMEs (range: 25–150 MMEs) (p < .001). Mean percent reduction in prescription size was greater in the Orthopaedic Surgery cohort (45% versus 38%) (p = .002). No significant difference was observed in the mean percentage of prescribed MMEs leftover between the two cohorts (Orthopaedic 47% vs. General 59%), (p = .07). Orthopaedic Surgery patients had higher mean MMEs consumed (126 MMEs) than General Surgery patients (26 MMEs) (p < 0.001). Conclusion Postoperative opioid prescriptions were reduced in both patient surgical cohorts, with a more pronounced impact in Orthopaedic Surgery patients. Despite the reduction, both groups reported substantial and comparable percentages of unused opioids, indicating a need for targeted adjustments to minimize unused opioids. Level of evidence IV.